A radio continuum and polarization study of the pulsar wind nebula CTB 87 (G74.9+1.2). Issue 1 (11th June 2020) - Kothes, R; Reich, W; Safi-Harb, S; Guest, B; Reich, P; Fürst, E
ABSTRACT: We present radio continuum and linear polarization observations of the pulsar wind nebula (PWN) CTB 87 (G74.9+1.2) with the Effelsberg 100-m Radio Telescope between 4.75 and 32 GHz. An analysis of these new data including archived low-frequency observations at 1420 and 408 MHz from the Canadian Galactic Plane Survey shows that CTB 87 consists of two distinct emission components: a compact kidney-shaped component, 14 × 8.5 pc 2 (7.8 × 4.8 arcmin 2 ) in size and a larger diffuse, spherical, and centrally peaked component of about 30 pc (17 arcmin) in diameter. The kidney-shaped component with a much steeper radio continuum spectrum is highly linearly polarized and likely represents a relic PWN. The diffuse component represents the undisturbed part of the PWN expanding inside a cavity or stellar wind bubble. The previously reported spectral break above 10 GHz is likely the result of missing large-scale emission and insufficient sensitivity of the high-frequency radio continuum observations. The simulation of the system's evolution yields an age of about 18 000 yr as the result of a Type II supernova explosion with ejecta mass of about 12 M⊙ and explosion energy of about 7 × 10 50  erg. We also found evidence for a radio shell in our polarization data that represents the blast wave that entered the molecular cloud complex at a radius of about 13 pc.